The IASA Racetrack Microtron Facility - Karabarbounis, A.; Avramopoulos, H.; Economou, D.; Filippa, A. V.; Filippas, T. A.; Gazis, E. N.; Hizanidis, K.; Maroulis, D.; Papadakis, N.; Papanicolas, C. N.; Rahmani, H.; Stiliaris, E.; et al. (HNPS Advances in Nuclear Physics, 2019)
The Institute of Accelerating Systems and Applications (IASA) is pursuing research and facilitates postgraduate studies in traditional and cross-disciplinary areas where accelerators play an important role. The first major facility of IASA, now under construction, is a 246 MeV two-stage CW Cascade microtron. The planned experimental programs and facilities include nuclear and particle physics, nuclear medicine, archeometry and material science.